Effectiveness of Deep Breath Relaxation Technique to Reduce Acute Pain in Spontaneous Post Partum Patients - Nur Fitriani, Revica; Wahyu Ningrum, Ema (Viva Medika, 2024)
The puerperium phase refers to the period immediately after childbirth for 6 weeks or 42 days, in which case the reproductive organs will undergo subtle changes that resemble the changes that occurred before pregnancy. The main factor causing the high maternal mortality rate is the lack of care and attention given to postpartum women. The purpose of this case study is to assess the effectiveness of breathing relaxation techniques in reducing acute pain in postpartum patients. This study used case study methodology to investigate the patient's experience during the nursing process. The nursing process includes nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. The results showed that deep breath relaxation for 2x24 hours, before the intervention, the patient complained of pain in the birth canal with a pain scale of 5 (moderate). After the intervention, the patient's complaints of pain in the birth canal decreased with a pain scale of 3 (mild). In conclusion, deep breath relaxation is effective as an effort to reduce the intensity/level of pain in postpartum patients.